2011
DOI: 10.1152/physiolgenomics.00253.2010
|View full text |Cite
|
Sign up to set email alerts
|

Multisite haplotype on cattle chromosome 3 is associated with quantitative trait locus effects on lactation traits

Abstract: Multisite haplotype on cattle chromosome 3 is associated with quantitative trait locus effects on lactation traits. Physiol Genomics 43: 1185-1197, 2011. First published September 6, 2011 doi:10.1152/physiolgenomics.00253.2010.-The goal of this study was to identify candidate genes and DNA polymorphisms for quantitative trait loci (QTL) affecting milk yield (MY), fat yield (FY), and protein yield (PY) previously mapped to bovine chromosome 3 (BTA3). To accomplish this, 373 half-siblings sired by three bulls p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 68 publications
(77 reference statements)
1
9
0
Order By: Relevance
“…Except for the effect on BTA15, all effects were chiefly for fat and protein concentration and had been found previously in the Australian Holstein population by Kemper et al (2015). The effect on protein percentage on BTA3 was localized to 23 to 24 Mbp, whereas previous studies found a QTL located between 25 and 45 Mbp (Ashwell et al, 2004;Cohen-Zinder et al, 2011).…”
supporting
confidence: 55%
“…Except for the effect on BTA15, all effects were chiefly for fat and protein concentration and had been found previously in the Australian Holstein population by Kemper et al (2015). The effect on protein percentage on BTA3 was localized to 23 to 24 Mbp, whereas previous studies found a QTL located between 25 and 45 Mbp (Ashwell et al, 2004;Cohen-Zinder et al, 2011).…”
supporting
confidence: 55%
“…Furthermore, Kolbehdari et al (2009) found an association between MY and LOC511740 (rs43709850), which is 1.2 Mb telomeric to RORC, and an association between the trait PP and the PDZK1 gene (rs41587408) (2.7 Mb telomeric to RORC). Those results are in positional disagreement with a recently published study combining fine mapping and resequencing for the detection of QTL for milk production traits on BTA3 in a Holstein dairy cattle family design by Cohen-Zinder et al (2011). They highlighted four candidate genes (RAP1A, ADORA3, OVGP1 and C3H1orf88) in the region 27.1-36.2 Mb between the microsatellites BL41 and TGLA263 as potentially underlying QTLs found for MY, FY and PY.…”
Section: Discussionmentioning
confidence: 58%
“…27 Although RAP1A is a regulator having an important role in the developing mammary gland, 28 not much is known about the mechanism involving this gene with bone metabolism. In their study, Cohen-Zinder et al 26 detected two polymorphisms located in the promoter region of bovine RAP1A and in intron 4 of the gene, which were significantly associated with milk yield and composition traits in dairy Holstein population. Note that, similar to this finding, other lactation genes were previously identified as the top signals for BMD.…”
Section: Molecular Link Between Bone Metabolism and Lactationmentioning
confidence: 99%
“…The gene is mapped to a quantitative trait locus located in bovine chromosome 3 (BTA3). 26 Interestingly, an integration of human GWAS and gene expression profiling performed by Hsu et al 27 revealed a locus on 1p13.2 (orthologous to BTA3) associated with osteoporosis-related traits, which harbors the same gene, RAP1A. SNPs within human RAP1A are strongly associated with narrow neck width in women.…”
Section: Molecular Link Between Bone Metabolism and Lactationmentioning
confidence: 99%